Study on preparation and properties of aramid/stainless steel fiber blended electromagnetic shielding fabric. (March 2020) - Wu, Yilin; Li, Yonggui; Ma, Wenxiao
Abstract: In order to develop electromagnetic shielding (EMS) fabric with high-performance, aramid / stainless steel fiber blended yarns were used to achieve it, and its electromagnetic shielding effectiveness (EMSE), flame retardancy and tensile properties were tested. The effects of fabric structure, fabric thickness, and fabric overlap angle on fabric properties were studied. The results showed that the plain weave fabric has the best EMSE among three kinds of fabrics with plain, twill and satin weaves. The EMSE of the satin weave is the worst. When the fabric thickness increased, the EMSE enhanced. The EMSE at the fabric overlap angle of 45° is the highest when the overlap angle is changed from 0° to 90°.